THE INFLUENCE OF INTELLECTUAL INTELLIGENCE, EMOTIONAL INTELLIGENCE AND SPIRITUAL INTELLIGENCE ON STUDENT ACHIEVEMENT IN MANAGEMENT STUDY PROGRAM STIE MANDALA JEMBER - Tamriatin Hidayah; Hary Sulaksono (MBA - Journal of Management and Business Aplication, 2022)
This study aims to see the influence of the variables intellectual intelligence, emotionalintelligence and spiritual intelligence on student achievement in the STIE Mandala ManagementStudy Program, either partially or simultaneously. The population of this study were students ofthe Management Study Program. The research sample was second, fourth, sixth and eighthsemester students. Non-probability sampling method, sampling technique is purposive sampling.The data analysis method used multiple linear regression. The conclusions obtained partiallyintellectual intelligence and emotional intelligence have a significant effect on studentachievement in Management Study Program, while spiritual intelligence has no effect on studentachievement in Management Study Program STIE Mandala. Simultaneously the three of themhave a significant effect on student achievement in the management study program of STIEMandala. The implications that can be formulated are the need to maintain and improve the threeintelligences related to their effect on learning achievement.Keywords: Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence, LearningAchievement.